App development using IoS iCloud : incorporating cloudkit with swift in xcode - Baruah, Shantanu; Baruah, Shaurya (Apress, 2022)
Create a professional looking app from start to finish that takes advantage of iCloud technology. Rather than working with Storyboarding for building your UI, you'll use code to build professional looking screens. Using code is standard for professional developers to fit form factor alignment across multiple screen sizes and other design constraints. First, you'll build a basic, functional UX screen. Then you'll incorporate iCloud with CloudKit for data persistence and private, public, and shared databases. Here your code-drive UI design will expand out to developing professional looking screens with animation. You'll also learn to work with reminder and notification boxes, sharing data between your users, and adding functionally for interaction with other Apps. Finally, you'll tackle testing and using Test Flight before publishing your app to the App Store. This book offers a practical guide for coders at any level who want to learn and create professional looking iOS apps leveraging the database features of iCloud and the numerous extensions that Apple provides in the Xcode environment. Create professional looking apps that are secure and your users will love! What You'll Learn Leverage CloudKit for Backend as a Service Handle Asynchronous processes Share data among users of your app with simultaneous modifications Who This Book Is For iOS developers familiar with the basics of Swift coding who want to work with iCloud databases or move into more advanced fields, such as using extensions or designing UX in code.